2003
DOI: 10.1016/s0735-1097(02)02973-x
|View full text |Cite
|
Sign up to set email alerts
|

A simple method for noninvasive estimation of pulmonary vascular resistance

Abstract: Doppler echocardiography may provide a reliable, noninvasive method to determine PVR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
442
3
12

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 541 publications
(470 citation statements)
references
References 20 publications
13
442
3
12
Order By: Relevance
“…However, previous validation studies correlating TRV/VTI RVOT to invasively measured PVR showed a robust correlation even in patients with increased right atrial pressure and pulmonary capillary wedge pressure. 3 Fourth, although after multivariate adjustment, increased PVR was independently predictive of heart failure hospitalization, the HRs for all-cause mortality and adverse cardiovascular events did not reach statistical significance. This may suggest a specific relation between PVR and incident heart failure in this patient population.…”
Section: Discussionmentioning
confidence: 83%
“…However, previous validation studies correlating TRV/VTI RVOT to invasively measured PVR showed a robust correlation even in patients with increased right atrial pressure and pulmonary capillary wedge pressure. 3 Fourth, although after multivariate adjustment, increased PVR was independently predictive of heart failure hospitalization, the HRs for all-cause mortality and adverse cardiovascular events did not reach statistical significance. This may suggest a specific relation between PVR and incident heart failure in this patient population.…”
Section: Discussionmentioning
confidence: 83%
“…2 On the other hand, formal radionuclide measurement of GFR was performed in the present series as serum creatinine has been considered as an inappropriate marker of renal function in nonazotemic cirrhotic patients.…”
Section: Dear Editormentioning
confidence: 90%
“…The peak tricuspid regurgitant velocity We calculated the echocardiographic PVR (WU) reported by Scapellato et al [2], that by Abbas et al in 2003 [3], that by Dahiya et al [4], that by Lindqvist et al [5], that by Abbas et al in 2013 [6], and that by our new method (PVR PR ) using the following equations: …”
Section: Echocardiographic Examinationmentioning
confidence: 99%
“…The systolic RV-right atrial pressure gradient can be noninvasively obtained using TRV [8], and it can be used to estimate the mean PA pressure as in the first and second Abbas [3,6], Dahiya [4], and Lindqvist methods [5]. However, a wide regurgitant orifice may develop most frequently in the tricuspid valve among the four cardiac valves, probably because of the easy distensibility of right heart structures around the tricuspid annulus [16,17].…”
Section: Kaga Et Al 12mentioning
confidence: 99%
See 1 more Smart Citation